2011
DOI: 10.1007/s00204-011-0730-1
|View full text |Cite
|
Sign up to set email alerts
|

Expression of hepatic and ovarian cytochrome P450 during estrous cycle in rats

Abstract: It is known that gender differences in drug metabolism are largely attributed to changes in sex and growth hormones. Serum concentrations of estradiol, progesterone, prolactin, follicle-stimulating hormone, and luteinizing hormone change markedly during the human menstrual cycle and the rat estrous cycle. However, little information is available regarding the effects of the human menstrual cycle or the rat estrous cycle on expression and activity of cytochrome P450 (CYP) isoforms. The present study was carried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 38 publications
0
9
0
Order By: Relevance
“…Prior studies have reported that a proestrous surge of prolactin did not change hepatic P450 expression and Stat5 activity, and that neither ablation of prolactin by bromocriptine nor direct injection of prolactin affected hepatic Stat5 activity (Choi and Waxman, 1999;Lee et al, 2012). Considering the short duration of proestrous prolactin surge, which consists of 2 hours of an early peak (350-550 ng/ml) and a following 4 hours of a lower plateau (250-300 ng/ml) (Murai et al, 1989), and the rapid metabolic clearance of prolactin in the rat, in which half-life time of prolactin was 3.9-5.2 minutes (Koch et al, 1971), or in the human (Sievertsen et al, 1980), it is not contradictory that a proestrous surge of prolactin or direct injection of prolactin, as well as a continuous basal level of prolactin that could be ablated by bromocriptine, did not influence the upregulation of expression of femalepredominant P450 genes or Stat5 activation in the liver.…”
Section: Discussionmentioning
confidence: 98%
“…Prior studies have reported that a proestrous surge of prolactin did not change hepatic P450 expression and Stat5 activity, and that neither ablation of prolactin by bromocriptine nor direct injection of prolactin affected hepatic Stat5 activity (Choi and Waxman, 1999;Lee et al, 2012). Considering the short duration of proestrous prolactin surge, which consists of 2 hours of an early peak (350-550 ng/ml) and a following 4 hours of a lower plateau (250-300 ng/ml) (Murai et al, 1989), and the rapid metabolic clearance of prolactin in the rat, in which half-life time of prolactin was 3.9-5.2 minutes (Koch et al, 1971), or in the human (Sievertsen et al, 1980), it is not contradictory that a proestrous surge of prolactin or direct injection of prolactin, as well as a continuous basal level of prolactin that could be ablated by bromocriptine, did not influence the upregulation of expression of femalepredominant P450 genes or Stat5 activation in the liver.…”
Section: Discussionmentioning
confidence: 98%
“…Furthermore, it primarily metabolizes endogenous hormones with respect to progesterone to 6ÎČ-hydroxyl progesterone by hydroxylation, estrone to 2-or 4-hydroxyestrone by hydrolysis and estradiol to estriol by hydroxylation in humans (Mikhailova et al, 2006;Sugiyama et al, 2019;Lu et al, 2020). CYP1A subfamily contains only two functional isoforms as CYP1A1 and CY-P1A2, and it has been addressed that CYP1A2 is expressed mainly in the liver; whereas the expression of CYP1A1 is mainly distributed outside the liver and involves the metabolism for aromatic hydrocarbon, CYP1A2 is expressed in the liver and metabolizes the aromatic amines and heterocyclic compounds (Wijnen et al, 2007;Lee et al, 2012;Lu et al, 2020). However, in recent days, the expression of CYP1A2 is identified in the pancreas and lung as well (Vukovic et al, 2016).…”
mentioning
confidence: 99%
“…Pregnancy was not confirmed before sample collection because cows would have only been in early pregnancy. At this stage, pregnancy is not expected to affect expression of the genes of interest, and previous experiments in rats indicate that hepatic mRNA concentrations from the CYP genes are not sensitive to changes in the estrous cycle (Lee et al, 2012). The HS environment differed only slightly from the first experiment (31-39°C, 20% humidity: minimum THI = 73, maximum THI = 80.5), whereas the PF animals remained in a constant environment of 20°C.…”
Section: Short Communicationmentioning
confidence: 83%